2013
DOI: 10.3390/molecules18089999
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Small Molecule Microarray and Confocal Microscopy Techniques for Live Cell Staining Fluorescent Dye Discovery

Abstract: Abstract:Discovering new fluorochromes is significantly advanced by high-throughput screening (HTS) methods. In the present study a combination of small molecule microarray (SMM) prescreening and confocal laser scanning microscopy (CLSM) was developed in order to discover novel cell staining fluorescent dyes. Compounds with high native fluorescence were selected from a 14,585-member library and further tested on living cells under the microscope. Eleven compartment-specific, cell-permeable (or plasma membrane-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Small molecule microarrays were constructed and prepared for screening as previously described. 57,58 Briefly, for printing with MicroGrid II mechanical microarray microspotter (BioRobotics, Cambridge, UK) chemically activated glass slides (Avicor Ltd., Szeged, Hungary) were used, which contain a treelike, branched dendrimer structure with reactive functional groups at the terminal position. 59 Fluorescent-labeled MTMR14 was prepared with Alexa Fluor 647 carboxylic acid succinimidyl ester (Molecular Probes, A-20106) as previously described.…”
Section: Discussionmentioning
confidence: 99%
“…Small molecule microarrays were constructed and prepared for screening as previously described. 57,58 Briefly, for printing with MicroGrid II mechanical microarray microspotter (BioRobotics, Cambridge, UK) chemically activated glass slides (Avicor Ltd., Szeged, Hungary) were used, which contain a treelike, branched dendrimer structure with reactive functional groups at the terminal position. 59 Fluorescent-labeled MTMR14 was prepared with Alexa Fluor 647 carboxylic acid succinimidyl ester (Molecular Probes, A-20106) as previously described.…”
Section: Discussionmentioning
confidence: 99%
“…Bar 10 μm. (Molnár and Kuntam et al, 2013) We have discovered an unusual spectral behavior of the chemical C2 during our microscopy analyses. Gradual relocalization of dye signal from mitochondria to cytoplasm (seen as diffused dye signal all over the cell except in the nucleus) and the nucleolus was observed when labeled cells were repetitively scanned with 633 nm laser at 50% intensity setting as shown in Figure 8.…”
Section: Intracellular Localization Confirmation By Colocalization Wimentioning
confidence: 83%
“…Bar 10 μm. (Molnár and Kuntam et al, 2013) We have observed that photoconversion was also inducible by illumination with the rhodamine filter set of the fluorescence microscope (510-550 nm green excitation). To confirm the nucleolar localization of the photoconverted C2 dye (denoted with an asterisk C2*), we have used co-staining on live cells, 1 h after photoconversion with a vital DNA dye Hoechst 33342 which displays a negative staining pattern at the RNA-rich nucleolar regions (arrows in Fig.…”
Section: Unusual Spectral Behavior Of Chemical C2mentioning
confidence: 97%
See 1 more Smart Citation
“…The prion protein's role in a particular cellular process, including those that are concerned with metal-PrP interrelations in ex-vivo and in-vivo systems are generally studied by either genetically ablating (Büeler et al, 1992;Haigh and Brown, 2006;Kim et al, 2005;Kuwahara et al, 1999;Rossi et al, 2001;Sakaguchi et al, 1996) or siRNA silencing (Loubet et al, 2012) while working on HeLa cells (Molnár et al, 2013)., and have used here similarly. The bright red immunofluorescence-staining pattern in the ZW 13-2 cells revealed that the prion protein was distributed on the surface of the cells, whereas no immunoreactivity was detected in the Zpl 2-1 cells.…”
Section: Resultsmentioning
confidence: 99%